PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH BERDASARKAN UU NO. 23 TAHUN 2014 - Patra, Rommy (TANJUNGPURA LAW JOURNAL, 2018)
The communityÂ  has the right to participate in the formulation of legislation, such as the Regional Regulation (Perda). The existence of community participation is an important element that becomes an element that can not be ignored in the implementation of Regional Government in this era of democracy and decentralization. As a legal instrument in the implementation of Regional Government, the Regional Regulation in its formation is expected to be not elitist which is only made by the Head of Region together with the DPRD but also must involve community participation. However, there are still obstacles in community participation in the formation of local regulations caused by factors within the community itself (internal), namely the ability and willingness of the community to participate, as well as external factors, namely the role of formal apparatus and institutions. In addition, there are at least two main issues that arise in the effort to apply community participation, namely: (1) determine the model and process of involvement that matches the policy to be taken; and (2) determine who / what institutions need to be involved. To overcome these obstacles, in order to increase the participation of the community there should be an expansion of access to information and transparency in the formation of local regulations and effective communication between the community and local government and DPRD as institutions that have the authority to form local regulations. Because only with the existence of transparency, participation, communication and accountability in forming local regulation, it can be expected to produce a participative and aspirational regulation with sociological needs of the community.